Left atrial volume, function and B-lines at rest and during vasodilator stress echocardiography. (3rd October 2022) - Prota, C; Ciampi, Q; Cortigiani, L; Campagnano, E; Wierzbowska-Drabik, K; Kasprzak, J D; Djordjevic-Dikic, A; Merli, E; Arbucci, R; Gaibazzi, N; D'Andrea, A; Citro, R; et al.
Abstract: Background: Left atrial volume index (LAVi), left atrial reservoir function assessed with global peak amplitude longitudinal strain (PALS), and B-lines at lung ultrasound are supplementary markers of left ventricular filling pressures. Aim: To assess the relationship between LAVi, PALS and B-lines at rest and peak vasodilator stress. Methods: A comprehensive dipyridamole stress echo was completed in 266 patients (187 male, 71%, age 65±10 years) with chronic coronary syndromes. LAVi was measured with the biplane disk summation method. PALS was measured from a single vendor with 2-dimensional speckle tracking echocardiography and expressed in % values as the mean of the 12 atrial segments from 4- and 2-chamber values. B-lines were assessed with the simplified 4-site scan in the third intercostal space, with global score from 0 to 40, and considered significant with global score ≥2 units. Results: During dipyridamole, LAVi decreased (rest= 26±14 ml/m 2 vs stress= 24±12 ml/m 2, p<0.001), PALS increased (rest= 33±8 vs stress= 38±10%, p<0.001), and B-lines were more frequent (rest= 0.4, median interquartile range 0–30, vs stress= 0.7, median interquartile range 0–30, units, p<0.001). There was a significant, linear, inverse correlation between LAVi and PALS both at rest (r=−0.301, p<0.001) and at peak stress (r=−0.279, p<0.001, see figure). At group analysis, peak B-lines were directly correlated with peak LAVi (r=0.151, p=0.017) and inversely correlated with peak PALS (r=−0.234, p<0.001). At individual patient analysis, 4/93 patients (4.3%) showed stress B-lines (black dots in figure) with normal LAVi (<34 ml/m 2 ) and preserved PALS (>42%). Conclusion: Vasodilator stress echocardiography with combined assessment of left atrial volume, function and pulmonary congestion is feasible with high success rate in patients with chronic coronary syndromes. Pulmonary congestion is more frequent with dilated left atrium with reduced atrial contractile reserve, but it may occur in a minority of patients with normal LAVi and normal PALS. Funding Acknowledgement: Type of funding sources: None.